In Defence of Plant Personhood - Hall, Matthew (2019)
The philosopher Michael Marder has asserted that animist engagement with plants involves a projection of human purposes and goals leading to veneration. He has also argued that an extension of a categorical concept of personhood underpins my previous work on plant personhood. This paper draws on the growing scholarship of animist traditions following the work of Hallowell to reject Marder's characterization of a naïve animist approach to plants. It draws on these insights from animist traditions to outline a relational plant personhood, which is fully realized only in grounded, situated relationships of care that seek to enable the flourishing of plants.
Keywords: Animism; Care; Ethics; Kinship; Personhood; Plants; relational autonomy; Subjectivity